Introducing english vocabulary to young learners through flashcards: evidence from Indonesian elementary school teachers - Sri Wahyuningsih; Naili Syarifatul Izzah (Jurnal Ilmiah Pendidikan Dasar)
Introducing English vocabulary to young learners, particularly those in elementary schools is crucial. The present study aims to introduce English vocabulary for elementary school students by using flashcard media viewed from the elementary school teachers’ perspectives. This study employed a qualitative descriptive approach. Data were collected by conducting semi-structured interviews with three teachers at elementary schools in Indonesia. In analyzing the data, we used several procedures consisting of listening to recorded interviews, conducting interview transcripts by reading the interview results to gain an understanding of data about digital-based mosques, interpreting data from the words of sources, and checking the accuracy of data from sources. To ensure data validity, we used source triangulation by matching data from both sources. The results revealed that flashcards could be used as a medium to introduce English vocabulary among elementary school students. In addition, it helps them comprehend and memorize English vocabulary. Interestingly, they felt enthusiastic about learning English using flashcards. The implication of the study was discussed.